Screening for dementia in Arabic: normative data from an elderly Lebanese sample. (16th February 2018) - Abou-Mrad, Fadi; Chelune, Gordon; Zamrini, Edward; Tarabey, Lubna; Hayek, Maryse; Fadel, Patricia
Abstract: Objective: Prevention and treatment of dementia is a global concern that requires involvement of international samples. The purpose of this study is to develop culturally sensitive norms based on normal older Lebanese adults using multiple cognitive screening measures translated into Arabic for regional use.Methods: Participants were 164 community dwelling older Lebanese adults without cognitive complaints. They were administered the following cognitive measures in Arabic: Alzheimer's Disease 8-item questionnaire, Montreal Cognitive Assessment, Mini Mental Status Exam, Modified Mini Mental Status, Brief Visuospatial Memory Test-Revised, Lebanese Digit Span, Cross-Linguistic Naming Test, and phonemic and semantic fluency tests.Results: Sample characteristics and descriptive statistics for the demographically unadjusted raw scores are first presented ( N  = 164). Same-form test-retest reliability for each test were computed for 24 participants retested over 2–5 weeks, with reliabilities ranging from .55 to .90; Cronbach alpha coefficients ranged from .34 to .93. Two sets of normative data were constructed. First, base-rates for demographically unadjusted raw scores for the 5th, 10th and 15th percentiles are presented to identify relatively rare occurring performances. Second, using standardized regression-based procedures demographically corrected normative information adjusted for age, education and sex were generated for normative interpretation.Conclusions: Adapting cognitive tests for use in culturally and linguistically diverse regions of the world not only requires careful translation of test instructions and materials, but construction of culturally sensitive local norms. Our normative data should allow for more accurate identification of cognitive impairment and dementia in Arabic-speaking patients, especially those living in Lebanon.